Analisis Efektivitas Rekrutmen PPPK di Kota Banjarbaru: Tantangan dan Strategi Peningkatan Kinerja BKPSDM - M. Harry Mulya Zein; Ardyansyah Wijaya; Sisca Septiani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study examines the performance of the Banjarbaru City Personnel and Human Resources Development Agency (BKPSDM) in the recruitment of Government Employees with Work Agreements (PPPK). Using a qualitative approach with descriptive methods, this study evaluates performance based on five indicators: productivity, service quality, responsiveness, responsibility, and accountability. The results show that although BKPSDM has implemented a merit-based recruitment system through Computer Assisted Test (CAT), several challenges are still faced, such as technical constraints in the online system, limited formation quotas, and applicants' lack of understanding of administrative requirements. The research also identified supporting factors such as the regulatory framework, technology implementation, and the active role of BKPSDM in providing clear information to applicants. Recommendations include strengthening technological infrastructure, expanding socialization, optimizing complaint mechanisms, and proposing additional formation quotas to match regional needs.